1838, Ordinances of the Trustees of the University of North Carolina, ch. 5, § 13 (Raleigh Register). - (:unkn) unknown (General Publisher, 1838)
Prohibited students from keeping any firearms or gunpowder at the college. Prohibited keeping, carrying, or owning any sword, dirk, sword-cane, or other deadly weapon. Prohibited use of firearms without the permission of the college president.
--
Keywords: SENSITIVE PLACES